2022
DOI: 10.3390/cancers14051127
|View full text |Cite
|
Sign up to set email alerts
|

Very Late Recurrence in Germ Cell Tumor of the Testis: Lessons and Implications

Abstract: Background. Very late recurrence (LR), i.e., >5 years after initial presentation, occurs in about 1% of patients with germ cell tumors of the testis (TGCT) and is associated with poor prognosis. Methods. We retrospectively reviewed the records of patients at the M. D. Anderson Cancer Center who developed LR > 5 years after their initial diagnosis of TGCT. Results. We identified 25 patients who developed LR between July 2007 and August 2020. The median age at the time of LR was 46 years (range, 29–61). Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…The retroperitoneum was the most common site of relapse (58 %) with the majority having bulky retroperitoneal nodal size >10 cm, similar findings have been reported in the literature. 18,19 Furthermore, retroperitoneal relapse was seen even in the patients who had a prior history of retroperitoneal lymph node dissection (RPLND) in our study, comparable with results documented by Moore et al 19 , further emphasizing the critical role of RPLND by an experienced surgeon in the management of testicular GCT. The patients who received adjuvant first line chemotherapy also had a significant disease relapse as compared to chemotherapy-naive patients, which are comparable with the findings addressed by Friedlander et al, emphasizing that chemotherapy before relapse was a statistically significant and clinically relevant predictor of inferior outcome due to difference in the biology of chemotherapy-naive patients at late relapse from that of patients with a prior history of chemotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…The retroperitoneum was the most common site of relapse (58 %) with the majority having bulky retroperitoneal nodal size >10 cm, similar findings have been reported in the literature. 18,19 Furthermore, retroperitoneal relapse was seen even in the patients who had a prior history of retroperitoneal lymph node dissection (RPLND) in our study, comparable with results documented by Moore et al 19 , further emphasizing the critical role of RPLND by an experienced surgeon in the management of testicular GCT. The patients who received adjuvant first line chemotherapy also had a significant disease relapse as compared to chemotherapy-naive patients, which are comparable with the findings addressed by Friedlander et al, emphasizing that chemotherapy before relapse was a statistically significant and clinically relevant predictor of inferior outcome due to difference in the biology of chemotherapy-naive patients at late relapse from that of patients with a prior history of chemotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of mature glial tissue is confirmed by anti-GFA immunostaining (Clone 6F2, dilution 1/1000), inset 10× F I G U R E 2 Nodules on the bottoms and the left leg with testicular teratoma were reported over 10 years from diagnosis. 13 These data and our case suggest that, in such an uncommon tumor, a longer follow-up may be warranted.…”
Section: Conflict Of Interestsupporting
confidence: 52%
“…4 However, the longest time to LR was reported to be 33.1 years. 7 Ehrlish et al reported, with median follow-up of 15 years without RPLND of 141 patients with nonseminoma who achieved normalization of serum tumor markers and radiographic remission (residual mass <1 cm) after induction chemotherapy, 12 patients had relapse, and 2 (1.4%) experienced LR beyond 10 years. 10 The pathological types were germ cell tumors with elevated AFP in 2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…7,13,14 The frequency of teratoma with STM increased in LR, accounting for 44% beyond 5 years after initial treatment. 7 Teratoma with STM was frequently found in the retroperitoneum, as well as in the testis. Necchi et al showed that, of 48 patients with teratoma with STM, teratoma with STM occurred in the retroperitoneum in 46%.…”
Section: Discussionmentioning
confidence: 99%